2020
DOI: 10.1038/s41598-020-76286-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of global end-diastolic volume index derived from jugular and femoral indicator injection: a prospective observational study in patients equipped with both a PiCCO-2 and an EV-1000-device

Abstract: Transpulmonary thermodilution (TPTD)-derived global end-diastolic volume index (GEDVI) is a static marker of preload which better predicted volume responsiveness compared to filling pressures in several studies. GEDVI can be generated with at least two devices: PiCCO and EV-1000. Several studies showed that uncorrected indicator injection into a femoral central venous catheter (CVC) results in a significant overestimation of GEDVI by the PiCCO-device. Therefore, the most recent PiCCO-algorithm corrects for fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…They concluded mean GEDVI decreases to 473-650 mL/m 2 (680 to 800mL/m 2 is considered normal) in most patients. 21,22,23,24,25 Consistent with this, Kingston and colleagues found IVC inspiratory diameters to be smaller and IVC collapsibility greater in severe malaria compared to healthy individuals. 26 This decrease in preload is likely due to fluid losses caused by fever, vomiting, diarrhoea and diminished fluid intake with impaired consciousness.…”
Section: Adultsmentioning
confidence: 82%
“…They concluded mean GEDVI decreases to 473-650 mL/m 2 (680 to 800mL/m 2 is considered normal) in most patients. 21,22,23,24,25 Consistent with this, Kingston and colleagues found IVC inspiratory diameters to be smaller and IVC collapsibility greater in severe malaria compared to healthy individuals. 26 This decrease in preload is likely due to fluid losses caused by fever, vomiting, diarrhoea and diminished fluid intake with impaired consciousness.…”
Section: Adultsmentioning
confidence: 82%
“…We observed a similar impact on CO TPTD , but not at the same magnitude as indicated by the enlarged area under the curve that would result from an increase in MTt and DSt. This could be due to the mathematic correction performed by the PiCCO software that takes a certain amount of recirculation into account [ 31 , 32 ]. This finding is in line with our previous report, where we found no influence of ECBF on the difference in measurements of cardiac SV by echocardiography and TPTD in patients with severe ARDS managed with V-V ECMO [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that measurement errors may be caused by a “loss of indicator” due to modifications of the distribution of the cold bolus injected into the venous bloodstream [ 23 , 24 , 25 ]. The loss of an indicator in PICCO, such as a mispositioning of the central venous catheter tip, might have influenced CI measurements [ 11 ].…”
Section: Discussionmentioning
confidence: 99%